Vascular Endothelial Growth Factor Level as A Predictor of Hepatocellular Carcinoma in Liver Cirrhosis Patients - Benyamin Lukito; Ivet Suriapranata; Pendrianto Pendrianto; Ali Sulaiman; Irawan Yusuf; FX Budhianto Suhadi; George Mathew; Ferry Sandra (The Indonesian Biomedical Journal, 2014)
BACKGROUND: Alpha-fetoprotein (AFP) has been used for hepatocellular carcinoma (HCC) diagnosis and screening, however, AFP has poor specificity. The extensive hypervascularity associated with HCC could be driven in part by the pro-angiogenic factor known as vascular endothelial growth factor (VEGF). Furthermore, invasiveness of certain HCC lesions has recently been linked to high levels of VEGF. Therefore, circulating VEGF levels of patients with liver cirrhosis (LC) and HCC were investigated and analysed.METHODS: An analytical cross sectional study was designed. Diagnosis of HCC and LC was performed using clinical criteria and findings obtained from B-mode ultrasonography (USG), computed tomography (CT) angiography, or magnetic resonance imaging (MRI). Blood were collected intravenously from all subjects. Obtained serum and plasma were stored in -80°C for following analyses: hepatitis B surface antigen (HBSAg), hepatitis C virus (HCV), alanine aminotransferase (ALT), total bilirubin, albumin, VEGF and AFP.RESULTS: Levels of VEGF and AFP were significantly higher in HCC group compared with LC group with p = 3.05 x 10-6 and p = 8.74 x 10-5, respectively. There was a significant positive correlation (p=0.029, r=0.309) between VEGF level and tumor size in HCC group. The area under curve (AUC) for VEGF level in HCC and LC groups was 0.771. In the level of median 435.6 pg/mL VEGF, the sensitivity was 50% and specificity was 86%. In the level of 199.99 pg/mL VEGF the sensitivity was 74% and specificity was 76%.CONCLUSION: The present findings suggested that VEGF level could be a useful marker for the presence of HCC in patients with LC.KEYWORDS: hepatocellular carcinoma, HCC, liver cirrhosis, LC, vascular endothelial growth factor, VEGF, alpha-fetoprotein, AFP